Analysis of printing product quality control using the seven tools method on CV. XYZ - Mayuki, Mayuki; Lengkono, Herman Prafda; Chandraa, Jacky; Sriwidadi, Teguh (Privietlab, 2024)
This research aims to identify the elements that influence product flaws in printing outcomes, comprehend the findings of a seven-tool analysis, and establish what can be done about the defects that exceed the limits applied. This descriptive study employs both qualitative and quantitative methodologies. This study was investigated using the Seven Tools analysis. This study's findings are research that can be conducted using the seven-tool method. The conclusion that can be taken is about four factors that affect product defect, obtained the analysis of seven tools to make quality control and improve human, machine, work methods, and raw materials.